Differential expression of calcium/calmodulin‐regulated SlSRs in response to abiotic and biotic stresses in tomato fruit. Issue 3 (19th February 2013) - Yang, Tianbao; Peng, Hui; Whitaker, Bruce D.; Jurick, Wayne M.
<x xml:space="preserve">Abstract</x> Calcium has been shown to enhance stress tolerance, maintain firmness and reduce decay in fruits. Previously we reported that seven tomato SlSRs encode calcium/calmodulin‐regulated proteins, and that their expressions are developmentally regulated during fruit development and ripening, and are also responsive to ethylene. To study their expressions in response to stresses encountered during postharvest handling, tomato fruit at the mature‐green stage was subjected to chilling and wounding injuries, infected with Botrytis cinerea and treated with salicylic acid or methyl jasmonate. Gene expression studies revealed that the seven SlSRs differentially respond to different stress signals. SlSR2 was the only gene upregulated by all the treatments. SlSR4 acted as a late pathogen‐induced gene; it was upregulated by salicylic acid and methyl jasmonate, but downregulated by cold treatment. SlSR3L was cold‐ and wound‐responsive and was also induced by salicylic acid. SlSR1 and SlSR1L were repressed by cold, wounding and pathogen infection, but were upregulated by salicylic acid and methyl jasmonate. Overall, results of these expression studies indicate that individual SlSRs have distinct roles in responses to the specific stress signals, and SlSRs may act as a coordinator(s) connecting calcium‐mediated signaling with other stress signal transduction pathways during fruit ripening and storage.